Association of Rosuvastatin Use with Risk of Hematuria and Proteinuria. Issue 9 (September 2022) - Shin, Jung-Im; Fine, Derek M.; Sang, Yingying; Surapaneni, Aditya; Dunning, Stephan C.; Inker, Lesley A.; Nolin, Thomas D.; Chang, Alex R.; Grams, Morgan E.
Significance Statement: Despite reports of hematuria and proteinuria with rosuvastatin use at the time of its approval by the US Food and Drug Administration (FDA), current labeling mentions dose reduction (maximum daily dose of 10 mg) only for patients with severe CKD. In this real-world study, 44% of patients with severe CKD were prescribed a higher dose of rosuvastatin than recommended by the FDA. Compared with atorvastatin, rosuvastatin use was associated with slightly increased risk of hematuria and proteinuria in a dose-dependent manner and slightly increased risk of kidney failure with replacement therapy; the cardiovascular benefits were similar. These findings suggest the need for greater care in prescribing and monitoring rosuvastatin, particularly in patients who receive high doses or who have severe CKD. Visual Abstract: Abstract : Background: Despite reports of hematuria and proteinuria with rosuvastatin use at the time of its approval by the US Food and Drug Association (FDA), little postmarketing surveillance exists to assess real-world risk. Current labeling suggests dose reduction (maximum daily dose of 10 mg) for patients with severe CKD. Methods: Using deidentified electronic health record data, we analyzed 152, 101 and 795, 799 new users of rosuvastatin and atorvastatin, respectively, from 2011 to 2019. We estimated inverse probability of treatment–weighted hazard ratios (HRs) of hematuria, proteinuria, and kidney failure with replacement therapy (KFRT) associated with rosuvastatin. We reported the initial rosuvastatin dose across eGFR categories and evaluated for a dose effect on hematuria and proteinuria. Results: Overall, we identified 2.9% of patients with hematuria and 1.0% with proteinuria during a median follow-up of 3.1 years. Compared with atorvastatin, rosuvastatin was associated with increased risk of hematuria (HR, 1.08; 95% confidence interval [95% CI], 1.04 to 1.11), proteinuria (HR, 1.17; 95% CI, 1.10 to 1.25), and KFRT (HR, 1.15; 95% CI, 1.02 to 1.30). A substantial share (44%) of patients with eGFR <30 ml/min per 1.73 m 2 was prescribed high-dose rosuvastatin (20 or 40 mg daily). Risk was higher with higher rosuvastatin dose. Conclusions: Compared with atorvastatin, rosuvastatin was associated with increased risk of hematuria, proteinuria, and KFRT. Among patients with eGFR <30 ml/min per 1.73 m 2, 44% were prescribed a rosuvastatin daily dose exceeding the FDA's recommended 10 mg daily dose. Our findings suggest the need for greater care in prescribing and monitoring rosuvastatin, particularly in patients who receive high doses or who have severe CKD.